bahan ajar,lingkungan,b.arab LINGKUNGAN BERBAHASA ARAB SEBAGAI INSTRUMEN PENGEMBANGAN BAHAN AJAR BAHASA ARAB UNTUK PELAJAR PEMULA - Muhammad Ajyad; Kamal Yusuf (AN-NAS, 2022)
Nowadays, the urgency of using Arabic language makes non Arabic society considering that learning Arabic language is a must especially for Muslims. Ignoring the environment function that applies the use of Arabic language is related as the pride and asset of education institution, however it also has functions such as motivation and learning source for students The researcher arranged this articel to prove that a good formed language environment could be used as a strategies and a factor in learning Arabic language skill. The reseacher used qualitative descriptive approach which was applied with literature review. Moreover, the observation has taken through by social media which some books and journal as resource are needed to find the turth and relevant informations about the main case. The result showed that developing learning media Arabic language for students based on environment could give a significant impact for students’ abilities in writing, reading, speaking or comprehending Arabic language. However in fact, everybody has a natural Language Acquisition Device which helps them easier in language skill. Moreover, that skill is determined by the environmental conditions around each student.